(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2020)
This Research Deals With “Interference Between Blood Money And Civil Compensation In Sharia And Law”; In Its Folds Highlight The Elements That Blood Money Shares With Civil Compensation, Considering It As Financial Right Of Victim Or His Family, In Its Appreciation Being Fair Compensation For The Crime. So, To What Extent Does It Overlap With Civil Compensation? And Since Judging Thing Was A Branch Of His Conception, We Began To Clarify The Essence Of Blood Money And Compensation, Then We Compared The Meaning Of The Two.We Concluded Finally That It In Event Of A Mistake Corresponds To Civil Compensation Arising From Tort Liability In Law, Despite The Elements That It Shares With Civil Compensation Doesn’t Mean They Are Two Sides Of The Same Coin, Rather, It Has Others Several Characteristics, Within Philosophy Of Punishment In Sharia, Which Modern Laws Have Been Unable To Do. Keys Words- Blood Money- Civil Compensation– Islamic Law – Law.